HDAC inhibition decreases XIST expression on female IVP bovine blastocysts - Oliveira, Clara Slade [UNESP]; Saraiva, Naiara Zoccal [UNESP]; Cruz, Maria Helena Coelho [UNESP]; Mazeti, Bruna [UNESP]; Oliveira, Leticia Zoccolaro [UNESP]; Lopes, Flavia Lombardi [UNESP]; Garcia, Joaquim Mansano [UNESP] (Oxford University Press (OUP), 2013)
During initial development, both X chromosomes are active in females, and one of them must be silenced at the appropriate time in order to dosage compensate their gene expression levels to male counterparts. Silencing involves epigenetic mechanisms, including histone deacetylation. Major X chromosome inactivation (XCI) in bovine occurs between hatching and implantation, although in vitro culture conditions might disrupt the silencing process, increasing or decreasing X-linked gene expression. In this study, we aimed to address the roles of histone deacetylase inhibition by trichostatin A (TSA) on female preimplantation development.We tested the hypothesis that by enhancing histone acetylation, TSA would increase the percentage of embryos achieving 16-cell stage, reducing percentage of embryos blocked at 8-cell stage, and interfere with XCI in IVF embryos. We noticed that after TSA treatment, acetylation levels in individual blastomeres of 8-16 cell embryos were increased twofold on treated embryos, and the samewas detected for blastocysts. Changes among blastomere levels within the same embryo were diminished on TSA group, as low-acetylated blastomeres were no longer detected. The percentage of embryos that reached the 5th cleavage cycle 118 h after IVF, analyzed by Hoechst staining, remained unaltered after TSA treatment. Then, we assessed XIST and G6PD expression in individual female bovine blastocysts by quantitative real-time PCR. Even though G6PD expression remained unaltered after TSA exposure, XIST expression was eightfold decreased, and we also detected a major decrease in the percentage of blastocysts expressing detectable XIST levels after TSA treatment. Based on these results, we conclude that HDAC is involved on XCI process in bovine embryos, and its inhibition might delay X chromosome silencing and attenuate aberrant XIST expression described for IVF embryos. © 2013 Society for Reproduction and Fertility.
Keywords: glucose 6 phosphate dehydrogenase; histone; histone deacetylase; transcription factor; trichostatin A; unclassified drug; X inactive specific transcript protein; animal cell; animal experiment; blastocyst; blastoma; cell culture; controlled study; cow; embryo cell; embryo development; embryo transfer; enzyme inhibition; female; fertilization in vitro; gene expression; histone acetylation; male; nonhuman; nucleotide sequence; preimplantation embryo; priority journal; protein expression; quantitative analysis; real time polymerase chain reaction; staining; X chromosome inactivation; Animals; Blastocyst; Cattle; Cells, Cultured; Female; Fertilization in Vitro; Glucosephosphate Dehydrogenase; Histone Deacetylase Inhibitors; Histone Deacetylases; Hydroxamic Acids; Models, Animal; RNA, Long Untranslated; X Chromosome Inactivation